FROM WORK CONDITIONS TO PERFORMANCE OUTPUT: THE EFFECTS OF WORK ENVIRONMENT AND INDIVIDUAL ABILITY ON EMPLOYEE PERFORMANCE: A Study of Sewing Line Employees at PT Karya Mekar Dewatamali - Sari, Adila Yunita (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2025)
This study examines the effects of the work environment and individual ability on employee performance among sewing line employees at PT Karya Mekar Dewatamali. The study employed an explanatory quantitative approach using a Likert-scale questionnaire survey administered to 66 employees. The work environment was measured through work atmosphere, physical facilities, subordinate–supervisor relations, and coworker relations (LK1–LK8). Individual ability was assessed through knowledge, training, experience, skills, and work capability (KI1–KI8). Employee performance was measured through quantity, quality, timeliness, attendance, and teamwork (KK1–KK10). The data were analyzed using multiple linear regression, with model adequacy evaluated through classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation. The findings show that the work environment is the most dominant factor and, together with individual ability, contributes positively to employee performance. The model explains a substantial proportion of the variance in performance (Adjusted R² = 0.702). These findings underscore the importance of workplace support and competency enhancement in repetitive and precision-based sewing tasks.